Dynamics of networks and its social aspects - Legara, Erika Fille T.
Complex networks have greatly contributed to understanding the dynamics and evolution of real-world systems and phenomena in both nature and society. In this work, we utilize and develop the different tools on complex networks to investigate social systems and phenomena that are relevant to our society. Particularly, the science of networks is used (1) to model and quantify multilevel marketing (MLM); and, (2) to simulate and optimize spread of information regarding family planning (FP) methods within society. For the first part of this work, our previous work on MLM schemes is completed. We provide an analytic treatment to the growth of binary and unilevel MLM based on branching process theory and validate the predictions using actual data. We also demonstrate that the structure of binary network is more robust to member quitting than unilevel. In the second part of this work, we construct an arbitrary social network where agents are defined by characteristics adopted from existing data on family planning methods in the Philippines (source: National Demographic and Social Health Final Report, 2003). The efficiency of random scheme in influencing a population in a social network to use contraceptives is contrasted with targeted scheme. In contrast with well-known results that targeted schemes (next individuals to be influenced is connected to the previous person contracted) in social networks allow faster and more efficient spread of information (or disease), our results demonstrate otherwise. We point to "bandwagon" type of behavior, neighbors are generally influenced by majority of their neighbors, as the unique dynamics that differentiate family planning information spreading, as compared for instance to epidemic spreading.
Computer print out.
Keywords: Online social networks; Social media